2019
DOI: 10.17263/jlls.668377
|View full text |Cite
|
Sign up to set email alerts
|

Peer editing as a way of developing ELT students’ writing skills: An action research

Abstract: Inspired from problematic nature of writing, this study adopted an action research through peer editing as a way of developing writing skills of students at an ELT department. This study was designed through the specific stages of an action research which are planning, action, observation and reflection. In planning and action stages, the researchers designed general and specific criteria to follow during the cycles, and they applied these criteria accordingly. In observation stage, the peer editing processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…The literature has shown that ESL/EFL students encounter a wide range of difficulties in writing (Fareed, Ashraf, & Bilal, 2016;Maznun, Monsefi, & Nimehchisalem, 2017). To help ESL/EFL students overcome difficulties in academic writing, researchers have examined the effectiveness of various pedagogical frameworks such as formative assessment, peer feedback and collaborative writing (Mohamadi, 2018;Saidon, Said, Soh, & Husnin, 2018;Yang, Badger, & Yu, 2006;Yüce & Ataç, 2019). Although collaborative writing has received noticeable attention from researchers, previous studies lack the focus on understanding ESL students' perceptions of the effectiveness of collaborative planning.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has shown that ESL/EFL students encounter a wide range of difficulties in writing (Fareed, Ashraf, & Bilal, 2016;Maznun, Monsefi, & Nimehchisalem, 2017). To help ESL/EFL students overcome difficulties in academic writing, researchers have examined the effectiveness of various pedagogical frameworks such as formative assessment, peer feedback and collaborative writing (Mohamadi, 2018;Saidon, Said, Soh, & Husnin, 2018;Yang, Badger, & Yu, 2006;Yüce & Ataç, 2019). Although collaborative writing has received noticeable attention from researchers, previous studies lack the focus on understanding ESL students' perceptions of the effectiveness of collaborative planning.…”
Section: Introductionmentioning
confidence: 99%
“…The current study provided opportunities for peerevaluation. Peer-evaluation or peer-editing enhances students' writing skills as they can explicitly or implicitly comment on their peers' writing production so they can reinforce their writing skills and contribute to developing other students' writing skills as well (Yüce & Aksu Ataç, 2019;Harutyunyan & Poveda, 2018;Ekmekci, 2017;Min & Xuemei, 2016). The concept of peer-editing in this study conforms to Vygotsky's social interaction concept.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Peer-editing is deemed one of the salient activities in the writing classroom. Peer editing enhances students' writing skills as it enables them to explicitly or implicitly comment on their peers' writing production so they can reinforce their writing skills and contribute to developing other students' writing as well (Siliwangi, 2019;Yüce & Aksu Ataç, 2019;Harutyunyan & Poveda, 2018;Ekmekci, 2017;Min & Xuemei, 2016).…”
Section: Editingmentioning
confidence: 99%
“…Writing consists of cognitive strategies and background knowledge of the target culture encouraging teacher to teach many components to the students. Writing also includes several processes requiring the writer to produce a comprehensible, clear, and informative written expression (Yuce and Atac, 2019). This skill involves the process of discovering ideas on the text not only by putting the words on the paper but also by selecting and organizing the ideas by considering several components.…”
Section: Introductionmentioning
confidence: 99%